Phenol production from wood wastes Vol. II of integrated plant complex - Mirandilla, Glenn (College of Engineering, 1982)
Site: Bislig, Surigao del Sur -- Capacity at maximum production: 19,063,200 kgs phenol/yr -- Floor area: 1,500 sq. meters -- Fixed capital investment: P 161.63 M (including pre-treatment section) -- Manufacturing costs at max. production: P 172.75 M/yr -- Sales at maximum production: P 199.61 M/yr